Mycobacterium abscessus subsp. massiliense mycma_0076 and mycma_0077 Genes Code for Ferritins That Are Modulated by Iron Concentration - Oliveira, Fábio M.; Da Costa, Adeliane C.; Procopio, Victor O.; Garcia, Wanius; Araújo, Juscemácia N.; Da Silva, Roosevelt A.; Junqueira-Kipnis, Ana Paula; Kipnis, André (Frontiers in Microbiology, 2018)
Mycobacterium abscessus complex has been characterized in the last decade as part of a cluster of mycobacteria that evolved from an opportunistic to true human pathogen; however, the factors responsible for pathogenicity are still undefined. It appears that the success of mycobacterial infection is intrinsically related with the capacity of the bacteria to regulate intracellular iron levels, mostly using iron storage proteins. This study evaluated two potential M. abscessus subsp. massiliense genes involved in iron storage. Unlike other opportunist or pathogenic mycobacteria studied, M. abscessus complex has two genes similar to ferritins from Mycobacterium tuberculosis (Rv3841), and in M. abscessus subsp. massiliense, those genes are annotated as mycma_0076 and mycma_0077. Molecular dynamic analysis of the predicted expressed proteins showed that they have a ferroxidase center. The expressions of mycma_0076 and mycma_0077 genes were modulated by the iron levels in both in vitro cultures as well as infected macrophages. Structural studies using size-exclusion chromatography, circular dichroism spectroscopy and dynamic light scattering showed that r0076 protein has a structure similar to those observed in the ferritin family. The r0076 forms oligomers in solution most likely composed of 24 subunits. Functional studies with recombinant proteins, obtained from heterologous expression of mycma_0076 and mycma_0077 genes in E. coli, showed that both proteins were capable of oxidizing Fe+2 into Fe+3, demonstrating that these proteins have a functional ferroxidase center. In conclusion, two ferritins proteins were shown, for the first time, to be involved in iron storage in M. abscessus subsp. massiliense and their expressions were modulated by the iron levels.